Heightened sympathetic neuron activity and altered cardiomyocyte properties in spontaneously hypertensive rats during the postnatal period - Haburčák, Marián; Harrison, Joshua; Buyukozturk, Melda M.; Sona, Surbhi; Bates, Samuel; Birren, Susan J. (Frontiers in Synaptic Neuroscience, 2022)
The Spontaneously Hypertensive Rat (SHR) has increased sympathetic drive to the periphery that precedes and contributes to the development of high blood pressure, making it a useful model for the study of neurogenic hypertension. Comparisons to the normotensive Wistar Kyoto (WKY) rat have demonstrated altered active and intrinsic properties of SHR sympathetic neurons shortly before the onset of hypertension. Here we examine structural and functional plasticity of postnatal SHR and WKY sympathetic neurons cultured alone or co-cultured with cardiomyocytes under conditions of limited extrinsic signaling. SHR neurons have an increased number of structural synaptic sites compared to age-matched WKY neurons, measured by the co-localization of presynaptic vesicular acetylcholine transporter and postsynaptic shank proteins. Whole cell recordings show that SHR neurons have a higher synaptic charge than WKY neurons, demonstrating that the increase in synaptic sites is associated with increased synaptic transmission. Differences in synaptic properties are not associated with altered firing rates between postnatal WKY and SHR neurons and are not influenced by interactions with target cardiomyocytes from either strain. Both SHR and WKY neurons show tonic firing patterns in our cultures, which are depleted of non-neuronal ganglionic cells and provide limited neurotrophic signaling. This suggests that the normal mature, phasic firing of sympathetic neurons requires extrinsic signaling, with potentially differential responses in the prehypertensive SHR, which have been reported to maintain tonic firing at later developmental stages. While cardiomyocytes do not drive neuronal differences in our cultures, SHR cardiomyocytes display decreased hypertrophy compared to WKY cells and altered responses to co-cultured sympathetic neurons. These experiments suggest that altered signaling in SHR neurons and cardiomyocytes contributes to changes in the cardiac-sympathetic circuit in prehypertensive rats as early as the postnatal period.